The Arabic, Hebrew, and Latin Reception of Avicenna's Physics and Cosmology - Hasse, Dag Nikolaus; Bertolacci, Amos (Scientia Graeco-Arabica ;, 2018)
The series is devoted to the study of scientific and philosophical texts from the Classical and the Islamic world handed down in Arabic. Through critical text editions and monographs, it provides access to ancient scientific inquiry as it developed in a continuous tradition from Antiquity to the modern period. All editions are accompanied by translations and philological and explanatory notes.